2011
DOI: 10.4319/lo.2011.56.2.0707
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mating behavior and temperature variation on the critical population density of a freshwater copepod

Abstract: At low density, population growth rates of dioecious zooplankton depend on the encounter rate of potential mates, resulting in a demographic Allee effect and a critical density for population establishment and persistence. Empirical evidence confirms a critical density for the calanoid copepod Hesperodiatomus shoshone, but existing estimates of the critical density span an order of magnitude. Combining three-dimensional video analysis of mating behavior with life history data from natural populations we estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Recent copepod-population growth models suggest that small population densities (Choi andKimmerer 2008, 2009) and biased sex ratios (Kiørboe 2007(Kiørboe , 2008 decrease copepod mating success and subsequent population growth by reducing mate-encounter rates (Kiørboe and Bagøien 2005;Visser and Kiørboe 2006;Kramer et al 2011). Here, we show in small (20-mL) vessels, where encounter rates are not limiting, that E. herdmani mating success is significantly reduced by the presence of a predator cue.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Recent copepod-population growth models suggest that small population densities (Choi andKimmerer 2008, 2009) and biased sex ratios (Kiørboe 2007(Kiørboe , 2008 decrease copepod mating success and subsequent population growth by reducing mate-encounter rates (Kiørboe and Bagøien 2005;Visser and Kiørboe 2006;Kramer et al 2011). Here, we show in small (20-mL) vessels, where encounter rates are not limiting, that E. herdmani mating success is significantly reduced by the presence of a predator cue.…”
Section: Discussionsupporting
confidence: 45%
“…Traditionally, population growth experiments have centered on the effects that environmental factors such as temperature and food concentration have on copepod egg production rate (Checkley 1980;Huntley and Lopez 1992;Mauchline 1998). However, more recent theoretical and experimental studies indicate that demographic factors, such as population density and sex ratio, also strongly affect population growth rates for copepods (Choi and Kimmerer 2008;Kiørboe 2008;Kramer et al 2008).…”
mentioning
confidence: 99%
“…Consistent with many studies (Keitt et al , Wang and Kot , Wang et al ), increasing the Allee parameter slowed the mean rate of spread. These and other studies, however, represented Allee effects using a constant value and our findings, motivated by growing recognition of spatiotemporal variability in Allee effects (Tobin et al , Kramer and Drake , Kramer et al , Walter et al ), add nuance to predictions of range expansion in heterogeneous landscapes. We found that spatial variations in Allee effects, and the structure of the variation, can drive deviations from predictions generated assuming a spatially constant Allee effect (Table , Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Despite difficulties of detecting demographic Allee effects (Gregory et al 2010), these theoretical predictions are supported by a number of empirical studies (Davis et al 2004, Taylor et al 2004, Tobin et al 2007, Lynch et al 2014. There is also growing evidence that Allee effects may vary in time and space (Angulo et al 2007, Tobin et al 2007, Kramer and Drake 2010, Kramer et al 2011, Walter et al 2015), yet theoretical studies have largely considered Allee effects to be constant. The present study investigates how spatial variability in Allee effects influences patterns of range expansion using a theoretical model simulated on different Allee effect landscapes.…”
mentioning
confidence: 99%
“…The processes associated with reproduction can be disturbed by increasing viscosity. By reducing their ability to accomplish biological processes, lower temperatures may reduce the fitness of the species (Kramer et al 2011). Con sequently, the lower temperature condition could significantly exert selective pressures governing T. longicornis behaviour.…”
Section: Ecological Consequencesmentioning
confidence: 99%